Pattern of Lymph Node Metastasis in Oral Cancer (Journal of Dhaka Medical College, 2021)
Background: Oral cancer is a common neoplasm worldwide which has a increased incidence and mortality rate over the past decades. In spite of skilled surgical and radio therapeutic modalities it is characterized by poor prognosis and a low survival rate. Lymph node metastasis is an important negative prognostic factor in oral cancer. In this study, pattern of cervical lymph node metastasis in oral carcinoma has been described. Such information may contribute to the understanding of oral cancer management plan.Methods: This cross-sectional observational study was conducted in the Otolaryngology and Head-Neck surgery department of Dhaka Medical College Hospital. The study period was from January 2018 to June 2018. A total of 50 patients were selected by purposive sampling technique. Data were collected by study physician himself. Then these collected data were recorded in structured case report forms. Clinical examination and relevant investigations were done. After planned surgical procedure post operative histopathological reports were collected. All collected questionnaire were checked very carefully. Data were processed and analyzed with the help of computer program SPSS and Microsoft excel. Quantitative data were expressed as mean and standard deviation and qualitative data as frequency and percentage. Comparison were done by tabulation and graphical presentation in the form of tables, pie chart, graphs, bar diagrams, histogram & charts etc.Result: Overall demographic features of 50 patients revealed that, the maximum incidence was seen in the age group 31-50 years (54.0%), mean age of the patient was 49.6 ±9.2 year. Male and female ratio was 4.5:1. In this study most of the tumors were well and moderately differentiated, 34.0% and 62.0% respectively. Aetiology and predisposing factors revealed that the most common were cigarette smoking, betal quid and alcohol consumption, present in 52.0%, 28.0% and 22.0% of patients respectively. Post operative histopathology reports showed that 24 patients (48.0%) had neck node metastasis among which 59.4% were with tumor size >1 cm. Tumors with the depth of invasion >3 mm had a very high risk of metastasis (P